Korean Medicine Subcision Therapies in Scar Treatment: A Retrospective, Multicenter Study at Network Clinics - Kim J; Lee JH; Jeong D; Lim T; Jung S; Paeng K; Lee S; Cho H; Lee S; Kim I; Kang B; Kim JH; et al. (Dove Medical Press, 2024)
Jungsang Kim,1,2,* Ju-Hyun Lee,3,* Dongbin Jeong,4 Taekyung Lim,4 Sangwoo Jung,4 Kwongil Paeng,4 Sangyoup Lee,4 Hyunki Cho,4 Seungyoup Lee,4 Ikdu Kim,4 Byungsoo Kang,5,6 Jae Hyo Kim,7 Hongmin Chu,8 Museok Hong4 1Department of Preventive Medicine, College of Korean Medicine, Kyung Hee University, Seoul, Republic of Korea; 2Daeat Korean Medicine Clinic, Suwon, Kyunggi-do, Republic of Korea; 3Department of Medical Support, Imsil-Gun Medical Center, Imsil, Jeollabuk-do, Republic of Korea; 4Rodam Korean Medical Clinic Network, Seoul, Republic of Korea; 5Daeat Korean Medicine Hospital, Seoul, Republic of Korea; 6Gachon University, Seongnam-si, Gyeonggi-do, Republic of Korea; 7Department of Meridian & Acupoint, College of Korean Medicine, Wonkwang University, Iksan-si, Jeollabuk-do, Republic of Korea; 8Korean Medicine Convergence Research Information Center for Stroke, College of Korean Medicine, Wonkwang University, Gwangju, Republic of Korea*These authors contributed equally to this workCorrespondence: Hongmin Chu, Korean Medicine Convergence Research Information Center for Stroke, College of Korean Medicine, Wonkwang University, Hoejaero 1140-23, Republic of Korea, Email hongminchu2@gmail.com Museok Hong, Department of Korean Internal Medicine, College of Korean Medicine, Wonkwang University, 460, Iksan-daero, Iksan-si, Jeollabuk-do, Republic of Korea, Email hongbar21@hanmail.netPurpose: This study is a retrospective, multicenter research designed to report the efficacy of Korean medicine subcision therapies in scar treatment.Patients and Methods: Charts and photographs of 29 patients who received subcision treatment between May 2016 and June 2020 in four scar treatment network clinics were analyzed. The Qualitative Global Acne Scarring Grade System (QGASC) and the Stony Brook Scar Evaluation Scale (SBSES) were used to objectively measure scar scores.Results: Except for 4 patients whose GASGS and SBSES scores remained unchanged, most patients' scars showed improvement from Visit 2 to about Visit 8. Furthermore, the degree of change for both scales was found to be statistically significant.Conclusion: Subcision therapy using acupuncture has been found to be an effective treatment for scar, with statistically significant improvements in patients' SBSES and QGASC scores.Keywords: scar, Korean medicine, subcision, acupuncture